German translation and validation of the complementary and alternative medicine health belief questionnaire (CHBQ) - Maximilian Hinse; Lea Jerzynski; Sylvia Binting; Sonja Kummer; Benno Brinkhaus; Gabriele Rotter (BMC Medical Education, 2024)
Abstract Background The Complementary and Alternative Health Belief Questionnaire (CHBQ) measures medical students’ attitudes towards Complementary Medicine (CM). The aim of the study was to examine the validity and reliability of the German translation of the CHBQ. Methods Data for the psychometric evaluation of the German translation were drawn from a study that investigated attitudes towards CM in (a sample of) medical students at Charité - Universitätsmedizin Berlin. Construct validity was determined via an exploratory factor analysis (EFA). Internal consistency was examined using Cronbach’s alpha and split-half reliability. Results The CHBQ was returned by 278 students, and was fully completed by 260 students (mean age 23.7 years; ± 4.3 SD), 69.2% were female). EFA revealed a single factor solution for all 10 items of the scale. All items, except one, had good item discrimination (range: 0.5–0.8), acceptable mean inter-item-correlation (0.39) and similar median correlation (0.38). Reliability was very good (α = 0.86) and further confirmed by split-half reliability (0.91). Conclusions The German version of the CHBQ is a valid and reliable instrument for measuring students’ attitudes towards CM.